Efektivitas Terapi Membaca Al-Fatihah Reflektif-Intuitif dalam Menurunkan Depresi Penyintas Autoimun - Infanti Wisnu Wardani; Fuad Nashori (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This study aims to observe the effectiveness of therapy of reflective-intuitive reading of Al-Fatihah in reducing the depression of autoimmune survivors. It used the quasi-experiment with the pre-test-posttest control group design – not non-randomized pretest-posttest control group design. The subjects involved in this study were the female Moslems becoming the survivors of one of the autoimmune diseases. Here, the level of depression of the subject was measured using the Depression Anxiety Stress Scale (DASS) sub-test of depression developed by Lovibond and Lovibond, adapted into the Indonesian language. The implementation of the therapy refers to the module of reflective-intuitive reading of Al-Fatihah developed by the researcher and team by referring to the module owned by Maulana, Subandi and Astuti. Data analysis used the Mann Whitney U-Test to determine the difference in the depression level in the experimental group before and after the intervention compared to the control group. The study results showed that therapy of reflective-intuitive reading of Al-Fatihah effectively reduced the level of depression of autoimmune survivors after passing the changing process taking a particular time.